Cloning of the Ajcaspase-8 Gene and Its Temporal Expression and Distribution Analyses During Embryonic Development in the Sea Cucumber Apostichopus japonicus - Xiaojing ZHANG; Chanchan ZHANG; Deyou MA; Jiayi LIANG; Meizhu YAO; Ziji LI (Progress in Fishery Sciences)
Metamorphosis is an essential stage during the ontogenesis of several important aquaculture animals, such as Apostichopus japonicus, and it covers a wide range of extensive alterations in the morphology and ecological behavior of larvae. Caspase-8 has been shown as the foremost apoptotic promoter, involved in embryonic development and immune defense processes in various aquatic animals, including fish and shellfish. To elucidate the function of the caspase-8 gene in the larval growth of the sea cucumber A. japonicus, RACE technology was employed to obtain its full-length cDNA, followed by analyses of its sequence characteristics. The expression levels of Ajcaspase-8 were assessed in adult tissues and during various larval development periods using real-time fluorescence quantitative polymerase chain reaction (RT-qPCR). Moreover, the expression localization of Ajcaspase-8 and the occurrence of cell apoptosis in metamorphosizing larvae were determined via whole embryo hybridization and TUNEL techniques, respectively. The results indicated that the full-length cDNA of the Ajcaspase-8 gene was 2, 790 bp, encoding 671 amino acids that included the hydrolytic active CASc domain and conserved pentapeptide QACQG characteristic of the Caspase family. Furthermore, a death receptor domain and two subunits (P20 and P10) were present in Ajcaspase-8 deduced protein, which acted as key motifs to perform the function of an initiator caspase in the apoptosis pathway. Ajcaspase-8 was clustered into a branch with Holothuria leucospilota, occupying a closer genetic distance to Oryzias latipes, indicating the advanced evolutionary status of this molecule. The RT-qPCR results showed that the Ajcaspase-8 gene in adult sea cucumbers exhibited housekeeping expression, with peak expression in coelomocytes and minimal expression in gonads (P < 0.05), indicating its involvement in immunity. During the entire developmental process of A. japonicus larvae, the expression of this gene was consistently detected, showing a peak value during the doliolarial stage and second-highest value during the juvenile stage (P < 0.05), both of which were significantly higher than those of other developmental stages (P < 0.05). This finding suggests that Ajcaspase-8 may play an important role in the morphological reshaping of larvae during metamorphosis. The in situ hybridization analysis showed that Ajcaspase-8 positive signals were exclusively localized in the stomach of late-stage auricularia, concentrated near the hyaline sphere of doliolaria, and greatly intensified in the intestines of juveniles. This indicated that this gene was actively expressed in the redundant and digestive tissues of larvae during metamorphosis. TUNEL visualization showed that the number of apoptotic cells increased with metamorphosis, suggesting that apoptosis was an important mechanism for maintaining the homeostasis of metamorphic larvae. Taken together, these results show that the Ajcaspase-8 gene is likely to play important roles in the metamorphosis and A. japonicus attachment, suggesting that it could initiate cell apoptosis to participate in morphological reconstruction and immune defense during the crucial process of ontogenesis in this species. This study provides fundamental data for further investigation of the regulatory mechanisms underlying metamorphosis in sea cucumbers.